The practice of a perspective-taking as an instrument of development - Marzanna Bogumiła Kielar (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2018)
The goal of the article is an analysis of the phenomenon of taking perspective as an instrument of development. The topic is described in the light of integral theory and constructive-developmental theory (S. Cook-Greuter's model). Both models present an evolutionary, vertical view of the practice of taking perspective: from narrow egocentric point of view till complex and rare worldcentric/kosmocentric view of reality. Then, the practice of taking perspective is presented in the context of self-development of postconventional leaders and how they support the development of others. Finally the Author outlines benefits and possible obstacles in the field of taking perspective. The results of the analysis can contribute to developing the aspects of consciousness (e.g. cognitive) in the practice of education.